A GLANCE BACKWARD AT RESEARCH IN ACCOUNTING. - Dein, Raymond C. (The Accounting Review, 1961)
Abstract American Accounting Association and its predecessor organization, The American Association of University Instructors in Accounting, have had as a primary objective the encouragement and promotion of research in accounting. On December 28, 1935, the regular business meeting of the twentieth annual convention of the American Association of University Instructors in Accounting was adjourned and the assembled members immediately reconvened in a business meeting and the members were shifted from the old organization to the new. The only changes that had been effected were the change of name and the adoption of a new set of By-Laws. The chief activities of the new Association were listed in the By-Laws as "publications and research." The first of the stated objectives of the Association was phrased thus: "To encourage and sponsor research in accounting and to publish or aid in the publication of the results of research."The means by which the American Accounting Association expected to encourage intensive research on accounting subjects was never fully faced. The Executive Committee did suggest a substantial, but very general, list of topics on which it was felt study was needed. It is quite evident that the master's and doctoral programs in accounting were looked upon as a source of research talent and effort which was readily available in quantity.